Pengaruh Current Ratio, Return On Asset, Debt To Asset terhadap Financial Distress Selama Masa Pandemi - Silvia, Dewi; Yulistina, Yulistina (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2022)
ABSTRACT Purpose - This study aims to analyze the influence of current ratio, return on assets, debt to asset ratio on financial distress during the pandemic in sub-sector companies listed on the IDX. Research Method - The sampling technique was purposive sampling based on these criteria, from a total population of 18 companies, 7 samples were obtained with an observation period of 6 years, 42 samples were obtained. Findings - The test results simultaneously show the effect of CR, ROA, DAR on financial distress in construction and building companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. Implication – The study provides information that can be used as a consideration for investors in making decision and presents a more complete analysis of financial ratios than previous studies.